Introduction Of Law No. 20 Of 2008 In Regulating Umkm To Students Of School Smp Jaf’ar Muslim - Yusuf Ahmad Aldi1; Yuniman Zebua; Siti Lam’ah Nasution (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
In the midst of increasingly rapid developments and is dominated by the development of information and communication technology that is very unstoppable. The state really hopes that Indonesian youth who will become the nation's next generation are able to master the development of science and technology (science and technology) so that they are not categorized as technologically stuttering youths (technological gaps). For young people, school is their starting place to find a way so that they can follow the development of science and technology (iptek). A lot of information that we can find through the internet that we can get after accessing the internet which is part of science and technology itself. One of them is about how to cultivate the souls of entrepreneurs to students so that later when they are in the midst of society they can become business actors who are able to create jobs. Micro and medium enterprises are initial businesses that can be done to support per capita income because micro and medium enterprises are businesses carried out by individuals, groups and small business entities. And Undang – Undang Nomor 20 Tahun 2008 which is the basis for the implementation of UMKM. In this study, the method used was a qualitative method which was carried out by way of socialization to SMP Ja'far Umslim Desa Lingga Tiga and the main targets were students of class IX. Atthe end of the socialization, the participants were given anget in the form of questions to fill in with a choice of yes or no answers. The results of the socialization showed that after the socialization was carried out there was a change in the participants' knowledge of UMKM and Undang – Undang Nomor 20 Tahun 2008.